Effect Of Return On Asset And Debt To Equity Ratio To Tax Avoidance In Company - Dahrani Dahrani (CERED Indonesia Institute, 2021)
The debt equity ratio shows the t-count statistical test value of 0.405, which is smaller than the t-table of 2.032, while the sig value of 0.688 is greater than 0.050, this indicates that the debt equity ratio has no effect on tax avoidance. The results of the research on return on assets and debt equity ratio together show the calculated F statistic value of 5.143 which is greater than the F table value of 3.280 while the sig value of 0.011 is smaller than 0.05, this indicates a significant influence between return on assets and debt equity ratio to tax avoidance simultaneously. This shows that return on assets has a positive and significant effect on tax avoidance. The debt equity ratio shows the t-count statistical test value of 0.405, which is smaller than the t-table of 2.032, while the sig value of 0.688 is greater than 0.050, this indicates that the debt equity ratio has no effect on tax avoidance. The results of the research on return on assets and debt equity ratio together show the calculated F statistic value of 5.143 which is greater than the F table value of 3.280 while the sig value of 0.011 is smaller than 0.05, this indicates a significant influence between return on assets and debt equity ratio to tax avoidance simultaneously. This shows that return on assets has a positive and significant effect on tax avoidance. The debt equity ratio shows the t-count statistical test value of 0.405, which is smaller than the t-table of 2.032, while the sig value of 0.688 is greater than 0.050, this indicates that the debt equity ratio has no effect on tax avoidance. The results of the research on return on assets and debt equity ratio together show the calculated F statistic value of 5.143 which is greater than the F table value of 3.280 while the sig value of 0.011 is smaller than 0.05, this indicates a significant influence between return on assets and debt equity ratio to tax avoidance simultaneously. 405 is smaller than t table of 2.032 while the sig value of 0.688 is greater than 0.050, this shows that the debt equity ratio has no effect on tax avoidance. The results of the research on return on assets and debt equity ratio together show the calculated F statistic value of 5.143 which is greater than the F table value of 3.280 while the sig value of.